Effectiveness of EMG use in pedicle screw placement for thoracic spinal deformities - Öner, Ali; Ely, Claire G; Hermsmeyer, Jeffrey T; Norvell, Daniel C (Evidence-Based Spine-Care Journal, 2012)
Study design: Systematic review.Objective: To determine the effectiveness of using electromyography (EMG) during intraoperative pedicle screw placement in patients with thoracic deformity. Methods: A systematic review of the English-language literature was undertaken for articles published between 1970 and July 2011. For our first question, we identified all articles that were designed to evaluate the diagnostic test characteristics (ie, measures of validity such as sensitivity, specificity, positive predictive value [PPV], negative predictive value [NPV]) of EMG for thoracic deformities in adolescent and adult patients. For our second question, we attempted to identify all articles that reported complication rates (pedicle wall breach or new neurological event) after pedicle screw placement in the same population comparing patients who did and did not undergo intraoperative EMG. Articles were excluded if they did not report or give raw data to calculate at least one of the four primary diagnostic test characteristics: sensitivity, specificity, PPV, or NPV for study question one. Articles were excluded if they did not have a “no EMG” control group for study question two. Other exclusions were reviews, editorials, case reports, non-English written studies, and animal studies. We rated the overall body of evidence with respect to each key question using a modified Grades of Recommendation Assessment, Development and Evaluation (GRADE) system for diagnostic and therapeutic studies.Results: The overall strength of evidence evaluating the diagnostic characteristics was low due to inconsistent findings between studies and uncertainty of the impact of false-negatives. The fairly low sensitivity may lead to a high-false negative rate. It is unclear what the impact of false-negatives would be since no neurological injuries were identified in the studies summarized. A higher specificity would suggest a fairly low false-positive rate; however, the rates could be as high as 30%. If sudden changes in treatment are required in the absence of any adverse event, this could be considered a limitation of such testing. The overall strength of evidence for evaluating the efficacy of EMG compared with no EMG was insufficient because of literature shortage on this topic.Conclusion: The overall strength of evidence evaluating the diagnostic characteristics was low due to inconsistent findings between studies and uncertainty of the impact of false-negatives. Given the low sensitivity and potential high rate of false-negatives, pedicle wall breaches may occur, without EMG notification. These undetected breaches may lead to loose or weak screw position which may lead to neurovascular complications during or after a translation-rotation maneuver, especially in rigid deformities. The higher sensitivity would suggest a lower rate of false-positives. We recommend considering the use of intraoperative EMG-monitoring method to help identify potential complications based upon available technology, personal experiences and preferences; however, surgeons should keep in mind that false-positive results may lead to increased surgery time and increased blood loss. The surgeon should not depend solely on EMG since it can also render false-negatives.